Pengembangan Bahan Ajar Semesta Sains Berbantuan Aplikasi Kahoot Terhadap Kemampuan Literasi Siswa SD - Lestari, Nabilla Dwi; Lian, Bukman; Aryaningrum, Kiki (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The aim of this research is to develop teaching materials about getting to know animals around us with the help of the Kahoot application in grade 3 elementary school that are valid and practical. This research uses the development method. By using the ADDIE development model, analyze, design, Development, Implementation, and Evaluation. The results of research on the validity of teaching materials based on material expert validation are 88.57% (very valid), linguist validation is 80% (valid), media validation results are 89% (very valid), practical validation is 95.5% (very practical) and effective validation 88.3% (very effective). Then the small group student response questionnaire assessment was 99% categorized as very good. The results of this research also measure the effectiveness of the science teaching materials developed. It can be seen from the pretest and posttest to measure it with field trials that it gets an average score of 88.3% and is in the very effective category. Based on what has been explained, the science teaching materials assisted by the Kahoot application are very suitable for use. The results of the research analysis of teacher and student responses obtained an average of 89.58% in the very practical category and a score of 88.3% in the very effective category. This shows that the teaching materials for the universe of science, assisted by the Kahoot application, let's get to know the animals around us, which were developed practically and effectively without revision, are also very practical and effective for use in the learning process at school.